PENGENDALIAN MUTU: IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA, OPTIMALISASI FUNGSI PENGENDALIAN DALAM DUNIA PENDIDIKAN - APRIYANTI WIDIANSYAH (Universitas Bina Sarana Informatika, 2019)
Research was conducted to explain the concept of quality control, understanding the role of human resources, and to know the implementation of quality control in education. Qualitative methods are used with the types of Descriptive Research. Results and discussion related to college research should be able to answer the needs of the labor problems of the present and the future. Human resources efforts in quality control can run effectively and efficiently, then the necessary planning are clear, complete and integrated. Therefore, an increase in the quality of education is not just the responsibility of the Government/State, but will be a shared responsibility between all components of the nation in realizing national development in education.